Task Specialization and Organizational Commitment: An Empirical Examination Among Blue-Collar Workers - Jamal, Muhammad (Relations industrielles / Industrial Relations, 1975)
The present study was undertaken to examine empirically the proposition that specialization in jobs negatively affects the organizational commitment of industrial blue-collar workers. The field work for this study was done among 377 production workers in six companies in Vancouver, British Columbia. The analysis of the data indicated clearly that workers in highly specialized jobs tended to be less committed to their employing organization than workers working on less specialized jobs. In addition, it was observed that task repetition and task simplification were, respectively, inversely related to workers' willingness to exert effort for the success of the employing organization and to workers* desire to remain in the employing organization for an indefinite period of time.